Parents' concerns about children are highly prevalent but often not confirmed by child doctors and nurses - Wiefferink Carin H; de Meer Gea; Reijneveld Sijmen A; Crone Matty R (BMC, 2008)
Abstract Background The aim of this study was to assess the prevalence in the general population of parents' concerns about the development of their child, to identify groups at risk and to assess the association between parents' concerns and professional judgement. Methods We obtained cross-sectional data on a Dutch nationally representative sample of children aged 14 months, 3 3/4, 5-6 and 8-12 years within the setting of routine well-child visits provided to the entire population. A total of 4,107 participated (response rate 85.3%). Data were about concerns that parents reported by questionnaire before the visit regarding behavioural and emotional problems, developmental delay, consequences of disease and contact with peers that needed professional assistance, and about the assessment of these domains by doctors and nurses during the visit. Moreover, we obtained data on parent-reported psychosocial problems using the Infant-Toddler Social and Emotional Assessment and the Child Behavior Checklist. Results Of all parents, 49.3% reported some concerns and 8.7% reported frequent concerns, most frequently on child behaviour. Frequent concerns were most likely to refer to young children, children from labour immigrant families, with fathers of medium educational level and in low-income families. The prevalence rates of professional-assessed parenting problems were much lower than parent-reported ones. The rates of psychosocial problems were highest in the case of shared concerns, but also higher if parents expressed concerns that were not confirmed by professionals. Conclusion A very large proportion of parents of young children have concerns regarding their child, but agreement on these concerns with child health professionals is relatively low.